Reflections on Progress: Some Methodological Notes - Loewenstein, Bedřich (Dějiny – teorie – kritika, 2024)
Using the form of an essay, the author gives an account of historical-philosophical thought on the idea of progress in the 20th century with the emphasis on its methodological grounding. He takes as his starting point John B. Bury´s theory, which defined the idea of progress in terms of secular intellectual climate. In opposition to this approach, he then looks with a critical overview at the contrary or polemic concepts put forward by Robert Nisbet, Karl Acham, Heinz-Dieter Kittsteiner or Johannes Rohbeck, which rehabilitate the history of philosophy and seek to identify the evaluative criteria of progress, one of the basic obstacles in thinking about the reality of progress. The author also devotes great attention to attempts to disconnect progress from subjective or culturally-based value judgements by using terms like "development" or "modernisation", while also considering critiques of these attempts at detail.